The housing stock, housing prices, and user costs: The roles of location, structure and unobserved quality - Jonathan Halket; Lars Nesheim; Florian Oswald (Centre for Microdata Methods and Practice (cemmap), 2020)
Which housing characteristics are important for understanding homeownership rates? How are housing characteristics priced in the rental and owner-occupied markets? And what can the answers to the previous questions tell us about economic theories of homeownership? Using the English Housing Survey, we estimate a selection model of the allocation of properties to the owner-occupied and rental sectors. Structural characteristics and unobserved quality are important for selection. Location is not. Accounting for selection is important for estimates of rent-to-price ratios and can explain some puzzling correlations between rent-to-price ratios and homeownership rates. These patterns are consistent with, among others, hypotheses of contracting frictions in the rental market likely related to housing maintenance.
Keywords: C31; R31; 330; Homeownership; Rents; Housing Supply; Selection; Immobilienmarkt; Wohneigentum; Mietwohnung; Standortfaktor; Immobilienpreis; England; London